Oziella - Chetverikov, Philipp E. (Zenodo, 2016)
Oziella cf rigida (Roivainen 1950) Roivainen 1950:17,18; fig.11 Chetverikov 2014:144,152 Living inside the leaf sheaths of Carex scita var. riishirensis (Franch.) Kük. 1909, collected from RUSSIA: Kamchatka Peninsula, Mil’kovsky District, 1 km east to settlement Atlasovo near Tolbachik volcanic complex, 21 August 2006, coll. P.G. Efimov, slides #K-3-06/1, #K-3-06/2 and #K-8-06/2, all stages numerous. Published as part of Chetverikov, Philipp E., 2016, New species and records of phytoptid mites (Acari: Eriophyoidea: Phytoptidae) on sedges (Cyperaceae) from the Russian Far East, pp. 367-380 in Zootaxa 4061 (4) on page 377, DOI:10.11646/zootaxa.4061.4.3, http://zenodo.org/record/264406